Case report of a COVID-19 family cluster originating from a boarding school - Citra Cesilia; Silvia Sudarmaji; Djatnika Setiabudi; Heda Melinda Nataprawira (Indonesian Pediatric Society, 2021)
Since it was first identified in Wuhan City, Hubei Province, China in December 2019, SARS-CoV-2 has spread to 195 countries and infected more than 8 million people globally. Indonesia, an archipelago consisting of thousands of islands and 34 provinces, has the largest number of confirmed cases and mortality in Southeast Asia. A total of 464 districts/cities in Indonesia have been affected by COVID-19, of which 189 districts/cities are considered to be local transmission areas. Riau Province, located in Sumatra Island, consists of 12 districts/cities with a population of more than 6.8 million. This province has the 1st largest number of COVID-19 cases on Sumatra Island. Currently, more than 3000 childrens have been infected with case fatality rate <0.3% and recovery rate >90%. In May 2020, the public health office of Riau reported that just 34 children were confirmed to have COVID-19, with symptoms varying from asymptomatic to moderate with only a few family clusters identified. During the pandemic, contact tracing is the main approach to detect and isolate sources of infection in order to reduce viral transmission. This method has also been used to control transmission of other respiratory diseases such as tuberculosis (TB), MERS, and SARS. We report here on a familial cluster of COVID-19 in the Meranti Island Regency, which is located 145 km from the city of Pekanbaru (Riau Province). The island can only be reached in four hours by speed boat.